CORRELATION OF THE OPTICAL PROPERTIES AND INTERBAND TRANSITION OF VANADIUM THIN FILMS (Biological Sciences - PJSIR, 2022)
The possibilities of using the optical constants nand k of vanadium thin films, to calculate the free-electronopticaleffective masses and relaxation time which were derived from the results, are discussed from the theoretical and experimentalpoint of view. Throughout the optical constants, the optical conductivity